2008
DOI: 10.1073/pnas.0805827105
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the fungal fatty acid synthase type I multienzyme complex

Abstract: Fatty acids are among the major building blocks of living cells, making lipid biosynthesis a potent target for compounds with antibiotic or antineoplastic properties. We present the crystal structure of the 2.6-MDa Saccharomyces cerevisiae fatty acid synthase (FAS) multienzyme in complex with the antibiotic cerulenin, representing, to our knowledge, the first structure of an inhibited fatty acid megasynthase. Cerulenin attacks the FAS ketoacyl synthase (KS) domain, forming a covalent bond to the active site cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
139
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(146 citation statements)
references
References 50 publications
5
139
1
1
Order By: Relevance
“…Refinement using the 3Á1 Å resolution structure by Leibundgut et al as a starting model resulted in the visualization of the additionally soaked classic FAS inhibitor cerulenin, which covalently binds to the active site of the KS. The remaining electron density for the PPT domain was located at the same position as observed by Lomakin et al (Johansson et al 2008 ;Leibundgut et al 2007 ;Lomakin et al 2007). Very recently, Johansson et al also reported the high-resolution structure of the isolated PPT domain from yeast FAS (Johansson et al 2009), which finally completes the atomic picture of the entire fungal FAS complex, apart from two flexible linkers and few solvent-exposed loops.…”
Section: Phasing and Map Interpretationsupporting
confidence: 78%
See 3 more Smart Citations
“…Refinement using the 3Á1 Å resolution structure by Leibundgut et al as a starting model resulted in the visualization of the additionally soaked classic FAS inhibitor cerulenin, which covalently binds to the active site of the KS. The remaining electron density for the PPT domain was located at the same position as observed by Lomakin et al (Johansson et al 2008 ;Leibundgut et al 2007 ;Lomakin et al 2007). Very recently, Johansson et al also reported the high-resolution structure of the isolated PPT domain from yeast FAS (Johansson et al 2009), which finally completes the atomic picture of the entire fungal FAS complex, apart from two flexible linkers and few solvent-exposed loops.…”
Section: Phasing and Map Interpretationsupporting
confidence: 78%
“…The Steitz lab obtained two crystal forms, a particularly radiation-sensitive monoclinic form (P2 1 , 217r347r263 Å 3 ) and bipyramidal tetragonal crystals in space group P4 3 2 1 2 with unit cell dimensions of a=b=231 Å and c=754 Å , which both diffracted weakly to 4 Å resolution (Lomakin et al 2007). The latter crystal form was also obtained in the Oesterhelt group with identical diffraction limits ( Johansson et al 2008). Leibundgut et al however, obtained tetragonal crystals with related unit cell dimensions of a=b=231 Å and c=784 Å , but now in space group P4 1 2 1 2, with a solvent content of 69 % and half a FAS particle per ASU, which diffracted to about 3 Å resolution.…”
Section: Purification and Crystallization Of Fungal Fasmentioning
confidence: 72%
See 2 more Smart Citations
“…Thus intracellular glutathione is present at millimolar concentrations, but even if it were desirable to selectively inhibit plasma FXIII-A with membrane impermeant reagents, glutathione is present at micromolar concentrations in plasma. However, cerulenin 2 which contains an epoxide moiety as its Cerulenin has previously been shown to inhibit the fatty acid synthase enzyme (FAS) complex, which involves covalent bond formation via attack of an active site cysteine thiol on the epoxide moiety within the natural product with subsequent ring opening [16]. In light of the interesting inhibitory properties displayed by cerulenin in the presence of FXIII-A, we were keen to explore the possible binding mode of this natural product with a view to designing variants that would be amenable to synthetic manipulation in order to enable SAR studies.…”
Section: Resultsmentioning
confidence: 99%